TO STUDY THE EFECT OF PREMENSTRUAL SYNDROME ON THE LIFESTYLE & DIETARY HABITS AND PRACTICES AMOUNG YOUNG FEMALES (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
A women goes through different hormonal changes in her body. As adolescence, changes takes place in the body to prepare for sexual reproduction. PMS is a series of emotional, physical and psychological symptoms that begin during a woman’s ovulation and usually terminate with the start of menstrual flow. Premenstrual signs are experienced by approximately 73% of women (Steiner&Pearlstein, 2000) and upto 40% experience symptoms severe enough to affect daily life. The study is conducted in NCR region indicate a higher prevalence of Premenstrual Syndrome(PMS) among educated women compared to domestic workers. Focusing on the symptoms of Premenstrual Syndrome(PMS), indicates that a significant majority of respondents, accounting for 55% ,had experienced mood swings. Conversely 10% were not experienced them . The study indicated that majority od respondents, 58 percent developed food cravings during premenstrual syndrome(PMS). Among respondents, 59% made changes in their dietary pattern during PMS, while 41% did not.